A physiological approach to understand the role of respiratory effort in the progression of lung injury in SARS-CoV-2 infection - Pablo Cruces; Jaime Retamal; Daniel E. Hurtado; Benjamín Erranz; Pablo Iturrieta; Carlos González; Franco Díaz (My University, 2020)
AbstractDeterioration of lung function during the first week of COVID-19 has been observed when patients remain with insufficient respiratory support. Patient self-inflicted lung injury (P-SILI) is theorized as the responsible, but there is not robust experimental and clinical data to support it. Given the limited understanding of P-SILI, we describe the physiological basis of P-SILI and we show experimental data to comprehend the role of regional strain and heterogeneity in lung injury due to increased work of breathing.In addition, we discuss the current approach to respiratory support for COVID-19 under this point of view.
Keywords: covid-19; lung strain; mechanical ventilation; p-sili; sars-cov2; work of breathing; coronavirus infections; critical care; disease progression; humans; lung injury; pandemics; pneumonia, viral; randomized controlled trials as topic; respiration, artificial; work of breathing; acute respiratory failure; biochemical analysis; breathing; coronavirus disease 2019; disease association; disease duration; disease exacerbation; disease severity; human; lung injury; mechanotransduction; mortality rate; positive pressure ventilation; priority journal; review; risk factor; artificial ventilation; coronavirus infection; disease exacerbation; intensive care; lung injury; pandemic; pathophysiology; physiology; randomized controlled trial (topic); virus pneumonia; work of breathing